Short and Long-Term Success of a Surgery Residency Prep Course - Crouch, Grace; Winter, Kelly; Quinn, Karson; Helmer, Stephen; McBoyle, Marilee (Kansas Journal of Medicine, 2023)
Introduction. The aim of our study was to evaluate the short-term and long-term effectiveness a surgery residency prep course has throughout intern year.Methods.  A surgery residency prep course was offered to graduating medical students.  An anonymous survey assessing perceived confidence in medical knowledge, clinical skills and surgical skills was given pre-course, post-course and at 6 months into residency.   Participants also completed a pre and post course quiz.Results.  Eleven students completed the course and participated in a pre-course survey, 7 completed the post-course survey and 4 completed the 6-month survey.  Students felt significantly more confident for intern year following the course compared to before the course (4.0 vs. 2.7, p = 0.018).  Students were found to have no significant change in perceived confidence at 6 months compared to post-course results (4.0 vs. 3.9, p = 0.197).  Objectively, post course quiz results were significantly improved compared to pre course quiz results (12.9 vs. 10.6, p = 0.004).Conclusions.  This study demonstrates the long-term effects a surgery prep-course may have on residents entering a surgery residency.